Morphology variation as a function of composition for blends of PVDF and a polyaniline derivative - Mattoso, LHC; Malmonge, L. F. (Elsevier B.V., 1999)
Blends of poly(vinylidene fluoride), PVDF, and poly(o-methoxyaniline), POMA doped with toluene sulfonic acid, TSA, were prepared by casting at various compositions and studied by scanning electron microscopy, X-ray diffraction and differential scanning calorimetry. The blend composition has a great influence on the morphology obtained. As the concentration of POMA-TSA is increased in the blend an interconnecting fibrillar-like morphology is formed and the spherulites characteristic of pure PVDF are destroyed. The variation of blend morphology is further discussed based on X-ray diffraction and differential scanning calorimetry analysis. (C) 1998 Elsevier B.V. Ltd. All rights reserved.
Keywords: conducting polymers; polyanilines; blends